HUBUNGAN KADAR LEUKOSIT DAN TOTAL LIMFOSIT DENGAN KELAINAN PARU PADA PASIEN COVID-19 - Andika Fauzan Putra; Rita Khairani (Jurnal Akta Trimedika, 2024)
Before the administration of vaccine, the impact of COVID-19 infection on the lungs was significant, affecting the prognosis and quality of life of patients. Identifying the severity of lung damage requires markers to identify the patient's condition early on, preventing further damage and abnormalities that may arise, especially in the lungs. The aim of this study is to reduce the occurrence of post-COVID-19 lung fibrosis by assessing the relationship between leukocyte and total lymphocyte levels and lung abnormalities in COVID-19 patients. The research method used is observational analytics with a cross-sectional design. The data used are secondary data, consisting of medical records of 112 COVID-19 patients as research subjects. The variables studied are leukocyte and total lymphocyte levels according to laboratory result, and documented lung abnormalities in medical records. The data is then analyzed using the Chi-square test with a significance level of p<0.05. Lung abnormalities, particularly pneumonia, are dominated by increased leukocyte levels in 62 individuals (91.2%) and decreased total lymphocyte levels in 63 individuals (94.1%). There is a significant association between leukocyte levels with lung abnormalities (p = 0.021), and total lymphocytes with lung abnormalities (p = 0.001).